Penerjemahan Bahasa Indonesia Ke Bahasa Jepang pada Kosakata Informasi Budaya dalam Objek Wisata di Istana Maimun Medan - Nasution, Laraiba; Hasibuan, Annalisa Sonaria; Mawaddah, Alvy (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2023)
This study discusses the translation of Indonesian into Japanese used in the tourist attractions at theMaimun Palace in Medan's cultural vocabulary. The issue at hand in this study is how to categorizetranslations from Indonesian, the source language (SL), into Japanese, the target language (BSa). Thepurpose of this study is to identify the types of translation as well as the translation of Indonesian, thesource language, into Japanese, the target language. In this study, a descriptive qualitative methodwas employed to gather data. The dialogue between one of the tour guides about the history of theMaimun Palace, a well-known tourist destination in the city of Medan, served as the research's sourceof data. In many ways, Maimun Palace still effectively preserves culture. In that civilization, materialculture such as traditional culture, which is concentrated and carefully preserved and which the palacefoundation promised to maintain, still holds the values and forms of material culture. According to thefindings of this study's data on translation categories, the writer will divide the cultural informationvocabulary categories obtained using Newmark's theory (1988), namely there is a category of Material(Artefacts) consisting of from 5 vocabulary in the building field, 4 vocabulary in place field, and 6vocabulary in equipment field after translating the Indonesian story into Japanese. Also included arethe Ecology category, which has 1 geographic vocabulary and 7 environmental/regional vocabulary,and the Social category, which has 4 greeting words, 2 job words, and 1 entertainment word.